An improvised apparatus and suggested activities for teaching sound waves - Rodriguez, Socorro Magallanes 1949- (1978)
The sound waves apparatus consists of a source of sound, a transmitter, and a receiver. The source is an improvised audio oscillator that gives four different frequencies, and is connected to a transmitter consisting of a speaker mounted at one end of the box about 1m by 0.04 meter square. To increase the sound, an amplifier is connected between the source and the speaker. The investigator tried out the apparatus and measured the four frequencies experimentally. To determine the accuracy of the values obtained, an oscilloscope was used. Activities on the different properties of sound waves using the improvised apparatus were tried out among twenty (20) fourth year high school students of Trinity College. Results showed that all the students were able to observe and gather data required by the activities. The investigator recommended the use of this apparatus in demonstrating wave concepts in high school.